2015
DOI: 10.1038/onc.2015.474
|View full text |Cite
|
Sign up to set email alerts
|

A new ER-specific photosensitizer unravels 1O2-driven protein oxidation and inhibition of deubiquitinases as a generic mechanism for cancer PDT

Abstract: Photosensitizers (PS) are ideally devoid of any activity in the absence of photoactivation, and rely on molecular oxygen for the formation of singlet oxygen ((1)O2) to produce cellular damage. Off-targets and tumor hypoxia therefore represent obstacles for the use of PS for cancer photodynamic therapy. Herein, we describe the characterization of OR141, a benzophenazine compound identified through a phenotypic screening for its capacity to be strictly activated by light and to kill a large variety of tumor cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
41
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(43 citation statements)
references
References 36 publications
(47 reference statements)
2
41
0
Order By: Relevance
“…We can observe that both regio-isomers have a quite similar behavior giving parallel elimination curves. Concerning the asymmetric carbon atom, as both isomers of both regio-isomers were shown to have similar activities [3], the developed method did not intend to separate Rand S-forms, and it is unlikely that isomerization at this position can occur during metabolization, but a difference in metabolizing enzymes affinity is not excluded between isomers.…”
Section: Pharmacokinetic Studymentioning
confidence: 99%
See 2 more Smart Citations
“…We can observe that both regio-isomers have a quite similar behavior giving parallel elimination curves. Concerning the asymmetric carbon atom, as both isomers of both regio-isomers were shown to have similar activities [3], the developed method did not intend to separate Rand S-forms, and it is unlikely that isomerization at this position can occur during metabolization, but a difference in metabolizing enzymes affinity is not excluded between isomers.…”
Section: Pharmacokinetic Studymentioning
confidence: 99%
“…1) in blood serum samples using a solid phase extraction (SPE) HPLC-UV method. As our findings showed that both regio-isomers of both OR-141-R and OR-141-S possess similar activities and selectivity [3], we decided to work on the racemic mixture of both regio-isomers and develop a method which would not separate R-and S-isomers. The method has been fully validated according to accuracy profiles based on tolerance intervals [4].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…HAP1 lysates were used for GlyGly immunoprecipitation using PTMScan Ubiquitin Remnant Motif Kit (Cell Signaling), according to manufacturer's protocol 45,46 . Briefly, 20 mg of extracts were solubilized and denatured in 10 mL lysis buffer (20 mM HEPES, pH 8.0, 9 M urea, 1 mM sodium orthovanadate, 2.5 mM sodium pyrophosphate, 1 mM β-glycerophosphate), reduced using dithiothreitol (4.5 mM final) for 30 minutes at 55 °C.…”
Section: Identification Of Isgylated Proteins Using Glygly Peptidomicmentioning
confidence: 99%
“…Protein ISGylation profiles in human cells have been previously reported, but with limited depth and predominantly based on overexpression systems [39][40][41][42][43][44] . To obtain deep coverage and modified residue information in a more physiologically relevant context, we decided to combine advanced proteomic techniques with the immunoaffinity purification of GlyGly tryptic peptides 45,46 in wild-type (WT) and USP18-/-knockout (KO) HAP1 cells, in order to analyse the first USP18-dependent ISGylome of human cancer cells. We uncovered novel ISGylated substrates that are controlled by USP18, further emphasizing its role as a master regulator of the innate immune response.…”
Section: Introductionmentioning
confidence: 99%